Pelatihan Implementasi Teknologi Informasi Untuk Menangkap Peluang Usaha Bagi Generasi Muda - Rozanna, Mira; Putra, Nanda Pramana; Fatiya, Nanda; Yuliansyah, Yuliansyah (Penerbit Goodwood, 2025)
Purpose: This community service program aimed to enhance the capacity of youth in Gadingrejo District by equipping them with knowledge and practical skills in utilizing information technology to identify and seize business opportunities. This initiative focused on addressing the digital literacy gap and promoting digital entrepreneurship as a strategy for local economic empowerment. Methodology: The activity was conducted through an interactive seminar and hands-on training. This approach involves multimedia presentations using LCD projectors, real-time demonstrations of digital tools, and active discussions. Participants were engaged in practical sessions to apply the concepts learned with guidance from the community service team. Results/Findings: The program successfully attracted enthusiastic participation from the youth, as evidenced by their active involvement in discussions, demonstrations, and question-and-answer sessions. Participants gained foundational knowledge about digital platforms such as e-commerce, social media, and digital financial tools and demonstrated an increased awareness of the potential of digital business models. Conclusions: The training created an inclusive, participatory learning environment that empowered the youth to view information technology as a critical asset for business innovation. This initiative served as a starting point for building a digitally competent entrepreneurial ecosystem at the local level. Limitations: The short duration of training limited the depth of technical skill development across all the digital tools introduced. The diversity in digital literacy among participants also presents challenges in delivering uniformly paced content. Contributions: This program contributes to digital inclusion by providing a replicable model of community-based ICT training targeted at youth entrepreneurship.